The "vision" Factor in Forest Development - Chatterjee, N. (Indian Forester, 1980)
The many facets of forest planning make it, at any time, a difficult task. Additionally, what often remains unrecognised is that the forest "capital" is liable to respond to the same saving-investment-output relationship that characterises all economic development activities. Thus, unless the capital base constituting the forest itself is expanded, or the production technology is improved, growth of output cannot be possible. For achieving this, appropriate reallocation of the present use to which skilled manpower and related resources are put, is essential. It is the thesis of this paper that only a planner with a deep concern for the future, possessing the necessary "vision", can take appropriate steps in this regard. To highlight the importance of this attribute in forest, development a relatively simple method of graphic presentation and analysis is followed. This makes it possible to articulate the various effects which different levels of the planners’ "vision" can have on the state of forests and their secular development, given the consumptional preferences of the society. Like any other theoretical enquiry, the analysis only helps in drawing certain possibly not immediately obvious, conclusions from alternative sets of hypothetical assumptions.